Bilateral Tibial Stress Fractures in a Young Man Associated with Idiopathic Osteoporosis - Case Report - Selahattin Özyürek; Erkan Kaya; Cengiz Yıldırım; Özkan Köse; Kenan Koca; Kenan Keklikci (Galenos Yayinevi, 2010)
Stress fractures are defined as a partial or complete fracture of bone due to an inability to endure a non-violent stress. Two factors have been proposed to explain the aetiology of stress fractures: muscle fatigue, and direct muscle action. We want to point to third factor with our case report: Osteoporosis. (From the World of Osteoporosis 2010;16:58-60)